2017
DOI: 10.1186/s40749-017-0023-z
|View full text |Cite
|
Sign up to set email alerts
|

Altered antioxidant enzyme activity with severity and comorbidities of chronic obstructive pulmonary disease (COPD) in South Indian population

Abstract: Background: Oxidative stress has been suggested in the pathogenesis of Chronic Obstructive Pulmonary Disease (COPD) with an additional burden of diabetes, hypertension and cardiovascular disease. In the present study, we investigated erythrocyte antioxidant enzymes activities in correlation to COPD severity and COPD comorbidities. Methods: One hundred twenty seven subjects with COPD and 59 healthy controls participated in this study. COPD severity was done based on the Global Initiative for Chronic Obstructive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
(58 reference statements)
1
8
0
Order By: Relevance
“…Our findings are consistent with clinical data; a study reported reduced GPx activity in smokers with COPD compared to healthy controls (smokers or non-smokers) [34]. GPx activity was also lower in COPD patients compared to healthy controls [35], in severe COPD compared to moderate disease [35, 36], and in moderate COPD compared to mild disease [35, 37]. Moreover, Golpon et al reported downregulation of the GPX3 gene in patients with severe emphysema [38].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are consistent with clinical data; a study reported reduced GPx activity in smokers with COPD compared to healthy controls (smokers or non-smokers) [34]. GPx activity was also lower in COPD patients compared to healthy controls [35], in severe COPD compared to moderate disease [35, 36], and in moderate COPD compared to mild disease [35, 37]. Moreover, Golpon et al reported downregulation of the GPX3 gene in patients with severe emphysema [38].…”
Section: Discussionsupporting
confidence: 91%
“…Glutathione (GSH), an antioxidant in the epithelial lining fluid [99], is an essential intermediate in the conversion of hydrogen peroxide to water and lipid peroxides degradation [100]. In addition, GSH might improve inflammation by inhibiting NF-κB activation.…”
Section: The Role Of Metabolism Dysfunction In Copd Pathogenesismentioning
confidence: 99%
“…Of these, 13 were further excluded, either because of missing information or they did not fulfil the inclusion criteria. Finally, 24 studies were included in the meta-analysis [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. A total of 2214 COPD patients (mean age 60 years, 74% male), and 1608 non-COPD subjects (mean age 55 years, 71% male) were evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies on 1329 COPD patients (mean age 60 years, 79% male) and 814 non-COPD subjects (mean age 54 years, 71% male) were identified [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. COPD was diagnosed according to the Global Obstructive Lung Disease (GOLD) guidelines in 12 studies [ 25 , 26 , 28 , 29 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], and the American Thoracic Society/European Respiratory Society (ATS/ERS) guidelines in three [ 27 , 30 , 39 ]. Thirteen studies assessed erythrocytes [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 37 , 39 ] whereas the remaining two assessed whole blood [ 36 , 38 ].…”
Section: Resultsmentioning
confidence: 99%